The Influence of Competence and Delegation of Authority on Employee Work Effectiveness at the Government Office of Sitahuis District, Central Tapanuli Regency - Natan Hesekel Tarihoran; Nelly Azwarni Sinaga; Muhammad Iqbal Batubara (Journal of Economics, Management and Accounting (JEMA), 2025)
In the era of modern bureaucracy, employee work effectiveness is a crucial factor in supporting fast, accurate, and efficient public services. Sitahuis District, as the frontline of public service in Central Tapanuli Regency, faces challenges of low work effectiveness, marked by delays in task completion, suboptimal service delivery, and lack of employee initiative. The main factors contributing to this condition are insufficient employee competence and a centralized delegation of authority that remains heavily dependent on the leadership. This study employs a quantitative approach using survey methods through questionnaires distributed to employees of the Sitahuis District Government Office. Data were analyzed using regression tests to examine the influence of competence and delegation of authority on employee work effectiveness. The results reveal that both competence and delegation of authority significantly affect work effectiveness, either partially or simultaneously. Descriptive analysis further indicates that both variables fall into the “good” category, although their implementation in daily practice has not yet reached optimal levels. The findings highlight that improving employee competence—such as technical and administrative skills—alongside implementing a clear, proportional, and accountable delegation of authority, can enhance productivity and service quality. This study is expected to provide theoretical contributions to the development of human resource management and practical recommendations for district-level leaders to improve employee effectiveness through targeted competence development programs and proper authority delegation mechanisms